(untitled) (MAUSAM, 1958)
In this paper the nocturnal variations in intensity of the airglow at the zenith sky at Poona obtained with a photoelectric method during the period 1954-56 have been reported, The measurements include those obtained without an optical filter and also those obtained with the monochromatic interference filters transmitting the oxygen emission line at, 5577 and the nitrogen band at), 4278 A. The measurements without the filter and with the), 5577 filter show a maximum of intensity before midnight while the blue emission does not show such a maximum but only shows a steady fall in intensity from the beginning to the end of the night. These results are wholly contradictory to those obtained by Karandikar in 1933 using photographic method. The results for, 5577 A emission are given in absolute units and are discussed in relation to those obtained by workers at other places in higher latitudes.